Orbital extramedullary leukemia relapse in a pediatric patient post‐CART cell therapy—Case report. (30th September 2020) - Essa, Mohammed F.; Alsultan, Abdulrahman
Abstract: CART therapy is an approved therapy in advanced ALL. The mechanism of relapse post‐CART therapy is under vigorous research. We report a 9‐year‐old boy who received CD19‐CART therapy after BM ALL relapse post‐HSCT. He presented with unilateral eye swelling which was initially managed as orbital cellulitis. Later on, it was proven to be an isolated ALL orbital relapse without peripheral blood B‐cell detection or BM involvement. Despite radiotherapy, he subsequently developed refractory CD19 positive ALL BM relapse. This case highlights the possibility of unusual relapse sites after CART‐therapy and that regular peripheral B‐cell monitoring is not enough to assure remission status. Better monitoring tools are needed to detect early disease relapse. Further understanding of the pathophysiology of isolated extramedullary relapse post‐CART therapy is warranted to improve the management of such challenging presentations.